Tree age influences nutritional, pectin, and anatomical changes in developing ‘Kinnow’ mandarin (Citrus nobilis Lour × Citrus deliciosa Tenora) fruit - Khalid, S.; Malik, A.; Singh, Zora; Ullah, S.; Saleem, B.; Malik, O. (Taylor & Francis, 2018)
© 2018 Taylor & Francis Group, LLC An understanding of variation in fruit quality in relation to tree age can help understand the issue of poor fruit quality in young orchards; however, limited information is available on the citrus fruit. In this study, the endogenous nutritional status in rind, rag, and leaves; pectin status in rind and rag; and anatomical fruit growth parameter in rind tissues were studied in ‘Kinnow’ mandarins fruit during their development on trees from three age (6-, 18-, and 35-year-old) groups. In older (35-year-old) trees, rind, rag, and leaf nitrogen (N), phosphorus (P), and potassium (K) concentrations were superior. In fruit from all tree age groups, total pectin and protopectin reduced; however water-soluble pectin (WSP) improved. In rind tissues harvested from young (6-year-old) trees, cell density was more while cell size was less. In all tree age groups, cell density in rind tissues correlated negatively with rind WSP.